Mathematical Modelling of Forestry Biomass Conservation and Wildlife Population Dynamics - Pathak, Rachana; Agarwal, Manju (Mathematics and Computer Science: Contemporary Developments Vol. 5, 2024)
Researchers have proposed various mathematical models to study forest depletion caused by resource-independent industrialization (population) by considering the spatial distribution of both forest biomass and the density of industrialization within a single homogeneous habitat. In this study, a non-linear mathematical model for the conservation of forestry biomass and wildlife population is developed and examined. The model assumes that the growth rate of wildlife conservation is directly proportional to the reduction of forestry biomass caused by the wildlife population. Additionally, in modelling process, the study investigate the impact of illegal trade on both forestry biomass and wildlife populations. The model equations are studied to understand the nature and stability of equilibrium points using the theory of nonlinear ordinary differential equations and numerical simulations. Moreover, sufficient conditions for the persistence of the system are derived through differential inequalities. The analysis reveals that the depletion of forestry biomass and wildlife populations can be mitigated through effective wildlife conservation. To achieve optimal results in wildlife conservation, it is crucial to minimize the rate of governance failure.